Assessing the Marketing Efficiency of Fresh Fruit Bunch (FFB) of Oil Palm by Independent Smallholders - Mirawati Yanita; Ira Wahyuni; Gina Fauzia; Karina Rahmah; Ulidesi Siadari; Siti Kurniasih; MA Rachmat Tanaka; Mukhlis (Postgraduate, University of Mataram, 2026)
Large oil palm production creates opportunities for independent smallholders; however, complex marketing chains and fluctuating prices often reduce farmers’ income and bargaining power. This study offers novelty by comparing the efficiency of three different fresh fruit bunch (FFB) marketing channels among independent smallholders in Mersam District, Batanghari Regency, while simultaneously evaluating marketing margins, farmer’s share, and marketing efficiency indicators within the local supply chain structure. A survey method was employed involving 55 independent smallholders selected using proportionate stratified random sampling, while marketing institutions were identified using snowball sampling. Marketing efficiency was analyzed using marketing margin, farmer’s share, and efficiency formulas. The findings identified three marketing channels: Channel I (smallholders–small collectors–large collectors–factories), Channel II (smallholders–large collectors–factories), and Channel III (smallholders–village unit cooperatives–factories). Channel III demonstrated the best performance with the lowest marketing margin (IDR 153/kg), the highest farmer’s share (92.24%), and the lowest efficiency value (4.07%), compared to Channel I with a marketing margin of IDR 248/kg and efficiency value of 6.48%, and Channel II with a marketing margin of IDR 167.43/kg and efficiency value of 4.10%. These results indicate that cooperative-based marketing channels are more efficient and provide greater benefits to smallholders. Simplifying marketing chains and strengthening institutional collaboration can improve farmers’ bargaining position and increase the share of FFB prices received by independent smallholders.